Secondary Data Analysis of National Surveys in Japan Toward Improving Population Health - Ikeda, Nayu (J Epidemiol, 2016)
Secondary data analysis of national health surveys of the general population is a standard methodology for health metrics and evaluation; it is used to monitor trends in population health over time and benchmark the performance of health systems. In Japan, the government has established electronic databases of individual records from national surveys of the population’s health. However, the number of publications based on these datasets is small considering the scale and coverage of the surveys. There appear to be two major obstacles to the secondary use of Japanese national health survey data: strict data access control under the Statistics Act and an inadequate interdisciplinary research environment for resolving methodological difficulties encountered when dealing with secondary data. The usefulness of secondary analysis of survey data is evident with examples from the author’s previous studies based on vital records and the National Health and Nutrition Surveys, which showed that (i) tobacco smoking and high blood pressure are the major risk factors for adult mortality from non-communicable diseases in Japan; (ii) the decrease in mean blood pressure in Japan from the late 1980s to the early 2000s was partly attributable to the increased use of antihypertensive medication and reduced dietary salt intake; and (iii) progress in treatment coverage and control of high blood pressure is slower in Japan than in the United States and Britain. National health surveys in Japan are an invaluable asset, and findings from secondary analyses of these surveys would provide important suggestions for improving health in people around the world.